Pendekatan Bidâ€™ah dan Ijtihad dalam Pembelajaran: Mengoptimalkan Kemampuan Berpikir Kreatif Peserta Didik - Moh. Muslih (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2018)
This paper offers the concept of â€˜creative educationâ€™ by employing an Islamic approach. In the Islamic perspective, creative education highlights two concepts, namely: â€œbidâ€™ahâ€ and â€œijtihadâ€. The meaning of these two concepts leads to several debates. This present study, therefore, tries to describe both the concepts so as to develop studentsâ€™ creative thinking skills in teaching and learning processes. This study promotes several endeavors that can be done by teachers to enhance the skills. Firstly, the teachers should be able to synergize their studentsâ€™ potential in terms of â€œruhâ€, â€œnafsâ€, â€œqalbâ€, and â€œaqlâ€ so that they emerge as individuals with the power of â€œmujtahidâ€. Secondly, they have to be capable of providing their students with an â€œijtihadiâ€ stimulus that may trigger the studentsâ€™ critical thinking skills by stimulating them to address questions. Thirdly, the teachers are expected to provide their students with chances of having ijtihad to explore lots of received information and new knowledge and convey their ideas and thoughts in a public space. Another effort is that they are expected to be able to manage meaningful opportunities to their students in order to perform creative thinking. It illustrates that the students may deliver a wide array of perspectives for a certain issue discussed. Finally, the teachers demonstrate positive appreciation for all the studentsâ€™ responses by regarding the principle that they attain two points for their appropriate response and one point for their inappropriate one dealing with the result of the studentsâ€™ ijtihad